Manifesta young women, feminism, and the future - Baumgardner, Jennifer 1970-; Richards, Amy 1970- (Farrar, Straus and Giroux, 2010)
Studies the history, politics, and popular culture surrounding feminism and discusses how feminism has changed in the twenty-first century.